2021
DOI: 10.1021/acssuschemeng.0c09184
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Desalination Capacity and Stability of Alkylamine-Modified Na0.71CoO2 for Capacitive Deionization

Abstract: Simultaneously regulating the physical properties and chemical environment of interlayer is a critical need for enhancing the capacity and stability of layered electrode materials in energy and environmental applications. Herein, the intercalation of n-alkylamine with different alkyl chain lengths to the structure of layered Na 0.71 CoO 2 (NCO) for application in capacitive deionization is reported. The amine intercalation via acid−base reaction routes allows the expansion of layer spacing of NCO, increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Currently, two‐thirds of the world's population live in water‐scarce areas. Desalination provides a direction for alleviating the water crisis, 4–7 and researchers have studied a variety of desalination technologies, such as multistage flash evaporation, 8,9 electrodialysis, 10–12 and reverse osmosis 13–16 . However, the disadvantages including high cost, high energy consumption, and secondary pollution of these technologies have restricted their further development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, two‐thirds of the world's population live in water‐scarce areas. Desalination provides a direction for alleviating the water crisis, 4–7 and researchers have studied a variety of desalination technologies, such as multistage flash evaporation, 8,9 electrodialysis, 10–12 and reverse osmosis 13–16 . However, the disadvantages including high cost, high energy consumption, and secondary pollution of these technologies have restricted their further development.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the CDI process, the desalination performance of HCDI has been greatly improved due to the higher sodium storage capacity of Faradaic material and attenuated “co‐ion expulsion” effect. Currently, various Faradaic electrode materials, including transitional metal oxides, 5,41 transition metal sulfides, 42,43 Prussian blues and their analogues, 44,45 and conductive polymer materials, 46 have been applied in HCDI and significantly improved the desalination performance.…”
Section: Introductionmentioning
confidence: 99%
“…38−40 In general, the drastic volume change of the stand-alone VO x during the ion intercalation process leads to poor structural stability, severely limiting its potential for the ECDI application. 30,41,42 Through the combination of VO x with nanocarbons to form a VO x -C hybrid nanomaterial, an amorphous structure provided by the carbon can be designed to effectively alleviate the strain-induced volume change of VO x to improve the structural stability. In addition, previous studies reported that the delicate structure of these composite electrode materials in the carbon matrix can effectively inhibit the disintegration of VO x nanoparticles (NPs) and maintain the structural stability during the intercalation process as well as facilitate ion diffusion, resulting in excellent electrochemical performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Vanadium oxide (VO x ), especially in the form of nanostructured materials, has attracted great interest because of its multiple oxidation states involving cation exchange can be used for charge storage in various potential windows. In general, the drastic volume change of the stand-alone VO x during the ion intercalation process leads to poor structural stability, severely limiting its potential for the ECDI application. ,, Through the combination of VO x with nanocarbons to form a VO x -C hybrid nanomaterial, an amorphous structure provided by the carbon can be designed to effectively alleviate the strain-induced volume change of VO x to improve the structural stability. In addition, previous studies reported that the delicate structure of these composite electrode materials in the carbon matrix can effectively inhibit the disintegration of VO x nanoparticles (NPs) and maintain the structural stability during the intercalation process as well as facilitate ion diffusion, resulting in excellent electrochemical performance. ,, Therefore, the modification of the structural design is a promising strategy to improve the desalination performance and stability of the ECDI application.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CDI has already been put into practical use for industrial desalination by commercial companies such as EST Water and Technologies (Changzhou, China) and Atlantis Technologies (Dana Point, CA, USA) [ 12 ]. Numerous studies about CDI have been carried out to upgrade the desalination efficiency of CDI [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, energy consumption, as a key parameter that directly determines the operation cost, has not received sufficient attention and has played a supporting role in addition to the desalination capacity in the research on CDI for a long period.…”
Section: Introductionmentioning
confidence: 99%